Pengurusan bahan buangan pembinaan : satu kajian kes projek pembinaan Jalan Simpang Pulai Lojing - Gua Musang-Kuala Berang - Mat Zin, Mohamad Alwi (2005)
The increasing awareness of environmental impacts from construction wastes has made waste management as an important aspects of construction project management. Various approaches for managing construction waste have been developed in the existing construction practices. The objectives of this study are to identify types of waste generated in road construction, to identify the problems in current construction waste management practice and to propose improvement to existing construction waste management practice. This study focuses on the activities related to flexible pavement type of construction; project located in nonurban area and construction activities related to earthworks, concrete works and formworks. The methodology of this study includes literature reviews and a case study, which covers interviews and site visits. The information gathered was compiled and analyzed where the types of wastes generated from earthwork, concrete work and formwork activities have been identified. These construction wastes were not managed properly due to lack of knowledge in waste management especially on the contractor side. Several recommendations to improve future construction waste management are given at the end of the study.